Thermal properties of Ti-doped Cu–Zn soft ferrites used as thermally actuated material for magnetizing superconductors. (23rd February 2016) - Stachowiak, P; Mucha, J; Szewczyk, D; Zhai, Y; Hsu, C H; Coombs, T A; Fagnard, J F; Philippe, M P; Vanderbemden, P
Abstract: A great majority of widely used ferrite ceramics exhibit a relatively high temperature of order–disorder phase transition in their magnetic subsystem. For applications related to the magnetization process of superconductors, however, a low value of T c is required. Here we report and analyze in detail the thermal properties of bulk Ti-doped Cu–Zn ferrite ceramics Cu0.3 Zn0.7 Ti0.04 Fe1.96 O4 and Mg0.15 Cu0.15 Zn0.7 Ti0.04 Fe1.96 O4 . They are characterized by a Curie temperature in the range 120–170 K and a maximum DC magnetic susceptibility exceeding 20 for the Cu0.3 Zn0.7 Ti0.04 Fe1.96 O4 material. The temperature dependence of both the specific heat C p and of the thermal conductivity κ, determined between 2 and 300 K, are found not to exhibit any peculiar feature at the magnetic transition temperature. The low-temperature dependence of both κ and the mean free path of phonons suggests a mesoscopic fractal structure of the grains. From the measured data, the characteristics of thermally actuated waves are estimated. The low magnetic phase transition temperature and suitable thermal parameters make the investigated ferrite ceramics applicable as magnetic wave producers in devices designed for magnetization of high-temperature superconductors.